2017
DOI: 10.3748/wjg.v23.i7.1215
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for gastric cancer patients of age 85 and older: Multicenter survey

Abstract: AIMTo investigate the surgical therapies for gastric cancer (GC) patients of age 85 or older in a multicenter survey.METHODSTherapeutic opportunities for elderly GC patients have expanded in conjunction with extended life expectancy. However, the number of cases encountered in a single institution is usually very small and surgical therapies for elderly GC patients have not yet been standardized completely. In the present study, a total of 134 GC patients of age 85 or older who underwent surgery in 9 related f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…Elderly patients usually have various comorbidities and therefore a shorter life expectancy than younger patients . In the present study, comorbidities such as hypertension and neurological diseases were more frequent in elderly patients than younger patients, and the ASA score tended to reflect the baseline diseases and comorbidities in each group.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Elderly patients usually have various comorbidities and therefore a shorter life expectancy than younger patients . In the present study, comorbidities such as hypertension and neurological diseases were more frequent in elderly patients than younger patients, and the ASA score tended to reflect the baseline diseases and comorbidities in each group.…”
Section: Discussionmentioning
confidence: 44%
“…Additionally, the Advanced Elderly Medical Service System in Japan, which provides benefits to reduce individual payments of medical expenses, also uses this cut‐off for applicants to qualify. The age of patients with gastric cancer has increased , and elderly patients often have comorbidities, such as circulatory and respiratory diseases, and a limited ability to engage in activities of daily living . Cancer therapies are crucial for elderly patients , but few large‐scale studies have evaluated the safety and feasibility of LG in elderly patients .…”
Section: Introductionmentioning
confidence: 99%
“…Randomized clinical trials, as well as many retrospective studies, have revealed advantages of laparoscopic gastrectomy over open gastrectomy in terms of early recovery, less pain, and fewer complications [ 5 10 11 ]. There have been several attempts to explore the feasibility of gastrectomy in elderly patients because of changes in the average lifespan globally [ 12 13 14 ]. Similar results for elderly patients, such as less blood loss and early recovery of the patients ≥80 years of age, have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The objective was to explore whether surgical treatment for specific elderly patients would be beneficial for their remaining lifespan. One study reported that non-cancer-specific deaths in elderly patients with clinical stage I gastric cancer could be negligible with laparoscopic gastrectomy [ 12 ]. In our study, 5 patients with stage I gastric cancer died of non-cancer-related reasons within a year of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3 Cancer-specific survival was 100% in clinical stage I. which can imply that this group died from non-cancer diseases. 4 Surgery with reduced nodal dissection in stage I disease also offered no significant difference in survival compared to standard surgery. 5 Furthermore, complications in patients who underwent curative surgery were more common in older age, especially medical complications, occurring in 7.4% of patients aged 80 years old or older compared to 2.2% of patients aged 60-64 years old 6 , particularly cardiac events and pulmonary complications, such as pneumonia and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%